2007
DOI: 10.1007/s11062-007-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in the human EEG during extralong physical activity

Abstract: In a single-case study, the effects of very long-lasting physical exercise, namely a 24-h-long ultramarathon, on the human electroencephalogram (EEG) were evaluated. While only effects of relatively short exercise have been reported earlier, we focused on the changes induced by these long-lasting physical requires. EEG was recorded repeatedly using an auditory oddball paradigm, and event-related potentials (ERPs), as well as changes in the current oscillatory brain activity (in particular, event-related desync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…demonstrated that walking altered cognitive task ERP amplitude and topography relative to a seated condition. Additionally, several studies have demonstrated that increased physical exertion requires additional cortical activation 1416 . Thus, as the locomotor task becomes more demanding, such as increasing physical demand with a load, more cortical resources may be allocated to the locomotor task.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that walking altered cognitive task ERP amplitude and topography relative to a seated condition. Additionally, several studies have demonstrated that increased physical exertion requires additional cortical activation 1416 . Thus, as the locomotor task becomes more demanding, such as increasing physical demand with a load, more cortical resources may be allocated to the locomotor task.…”
Section: Introductionmentioning
confidence: 99%
“…This transient enhancement was followed by a decline in amplitude and an increase in latency by 120 minutes, with both measures returning to baseline by the end of the three hours. Similarly, Doppelmayr et al (2007) noted a consistent decline in amplitude and prolongation in latency throughout a 24-hour treadmill run, though this study involved only a single participant. These results suggest that while exercise can initially enhance cognitive functions, it may eventually lead to fatigue effects that temporarily diminish cognitive efficiency, as reflected in the alterations in P300.…”
Section: Introductionmentioning
confidence: 70%
“…Considering that many recent research papers about functional anatomy, emphasized strong connections between motor cerebral areas and pre-frontal ones and that professional training performed on a period of time longer than 5 years, produced cerebral hemispheres functional plastic modifications,this connection worth to be study from now on (Doppelmayr & Doppelmayr, 2008).…”
Section: Introductionmentioning
confidence: 99%